Penggunaan Kaedah Dinamik Ultrasonik bagi Menentukan Pemalar Kenyal Kayu Tropika - Abd. Aziz, Sidek; Shaari, Abdul Halim; Chow, Sai Pew (Universiti Putra Malaysia Press, 1995)
This paper reports the determination of elastic constants for 56 tropical wood species using the dynamic ultrasonic technique. Longitudinal waves (45 kHz) were used to measure the velocity in the radial (R), tangential (T) and longitudinal (L) anisotropic directions of each sample of wood. The diagonal elastic constants of each species of wood studied were estimated using the values of ultrasonic wave velocities and their mean densities via the Christoffel equations. The results show that there is a linear correlation between the elastic constants in the L, Rand T directions and density of wood. Comparison between the ultrasonic measurement and static measurement indicate that the ultrasonic measurement technique is also capable of assessing the quality of tropical medium and heavy hardwood.